Title IX Literacy: What Coaches Don’t Know and Need to Find Out - Staurowsky, Ellen J.; Weight, Erianne A. (Journal of Intercollegiate Sport, 2011)
Celebrated by many and lamented by a vocal few, Title IX holds the distinction of being one of the few pieces of legislation passed by the United States Congress that has emerged as an iconic symbol unto itself. Despite broad familiarity with the term, it remains much less clear how many Americans have more than a superficial understanding of what the law requires. This study was pursued to determine the level of Title IX literacy among a constituency directly impacted by compliance or noncompliance with the legislation, that being college coaches. Results reveal that most college coaches do not have a basic knowledge of the application and extent of the law, have not been educated about Title IX through reliable educational mediums, and possess a desire to learn more and have candid and meaningful discussions about these issues. The lack of consistent and systematic education mechanisms may explain the tensions that arise so frequently around gender equity issues within college and university athletic departments.